Choice of Law Clause in Foreign Investment Contracts for The Development of The Nusantara Capital City - Angela, Krisna (Jurnal Suara Hukum, 2024)
This research analyses foreign investment within the context of the Nusantara Capital City (Ibu Kota Nusantara, IKN) development projects, focusing specifically on the application of choice of law clauses in resolving disputes arising from foreign investment contracts. Employing both statutory and conceptual approaches, the study explores how the IKN's green forest city concept aligns with national investment policies, making it conducive to foreign investment provided that projects adhere to legislative requirements and procedural guidelines. The findings underscore the critical importance of carefully crafted dispute resolution clauses, particularly those specifying the choice of applicable law, given the inherent complexity of contracts involving multiple parties subject to diverse legal systems. Effective dispute resolution mechanisms are essential for ensuring clarity and consistency in addressing potential legal conflicts that may arise in the course of international investment activities within the IKN development framework.